126 W fiber laser at 1018 nm and its application in tandem pumped fiber amplifier. (18th November 2016) - Yang, Hening; Zhao, Wei; Si, Jinhai; Zhao, Baoyin; Zhu, Yonggang
Abstract: We report on a 126 W fiber laser operating at 1018 nm with an optical efficiency of 75%. The optimal length for such a fiber laser is theoretically analyzed using steady-state rate equations including amplified spontaneous emission. Excellent agreement on the maximum output power is achieved between the numerical result and the experimental counterpart. Furthermore, a monolithic tandem pumped fiber amplifier is established by using conventional 30/250 μ m double clad ytterbium-doped fiber, and 185 W output power with 85% optical efficiency is realized.